Degradation of triclosan by anodic oxidation/in-situ peroxone process: Kinetics, pathway and reaction mechanism. (June 2021) - Qu, Chao; Ren, Na; Zhang, Shu-jun; Li, Yan-gang; Meng, Shu-juan; Li, Xiao-hu; Wang, Shan-quan; Liang, Da-wei; Li, An-ran
Abstract: Triclosan (TCS) is an emerging contaminant that threatens the environment and human health. This study was conducted to investigate TCS abatement by a novel electro-oxidation (EO) process, which used a Ti-based nickel and antimony doped tin oxide (NATO/Ti) anode and a carbon nanotubes (CNTs) doped carbon/PTFE (CNTs-C/PTFE) gas diffusion electrode (GDE) for oxygen reduction reaction (ORR). A comparative study was also performed for TCS degradation by using a traditional EO with a nickel foam cathode, termed as HER-EO. The optimal initial TCS concentration, current density and solution pH for TCS degradation during the ORR-EO and HER-EO were investigated. Results showed that ORR-EO removed more than 98% of TCS in 10–60 min under the concentration of 5–50 mg/L. The TCS degradation followed pseudo-first-order kinetics and its main intermediates were observed during the ORR-EO and HER-EO using liquid chromatography combined mass (LC-MS). The results of FED analysis and toxicity prediction by ECOSAR software showed that less intermediates accumulated during the ORR-EO and the residues were less harmful. The ORR-EO degradation mechanism for TCS was attacking on the ether bond and the benzene ring by OH. This novel ORR-EO process exhibits a great merit in the field of emerging contaminants abatement. Graphical abstract: Image 1 Highlights: Anodic oxidation/ in-situ electro-peroxone process was applied for removing TCS. More than 98% of TCS was removed in ORR-EO. TCS was attacked on ether bond and the benzene ring by OH. Possible pathway was proved by frontier electron densities calculations. ECOSAR analysis showed less toxicity of TCS and its intermediates in ORR-EO.